Correlation between the Macronutrient Content of Dental Calculus and the FFQ-Based Nutritional Intake of Obese and Normal-Weight Individuals - Ignatius Setiawan; Dian Lesmana; Dewi Marhaeni Diah Herawati; Irna Sufiawati; Sunardhi Widyaputra (International Journal of Dentistry)
The growing epidemic of chronic diseases afflicting both developed and developing countries is related to diet and lifestyle. The current dietary assessment still has many constraints, particularly related to the objectivity of data gathering. Dental calculus, which is usually considered as medical waste in dental treatment, turns out to be a provider of abundant oral information. The objective of this study is to obtain the correlation between the macronutrient content of dental calculus and nutritional intake based on FFQ. This research is an analytic observational study with a case-control study design. Samples consisting of 35 obese individuals and 21 normal-weight individuals were taken using purposive sampling. The nutritional intake data were obtained using FFQ. The macronutrient content of dental calculus was checked using a colorimetric assay. The comparison between obese individuals and normal-weight individuals was tested using the Mann–Whitney test and T-test. The correlation between the macronutrient content of dental calculus and nutritional intake based on FFQ was measured using Spearman’s rank-order correlation. The results showed there was a correlation between the macronutrient content of dental calculus and macronutrient intake based on FFQ. However, strong correlation was found only between fat intake with the total lipid content of dental calculus with rs = 0.521 and between carbohydrate intake with the total carbohydrate content of dental calculus with rs = 0.519. It was concluded that carbohydrate, protein, and lipid intake can be assessed using dental calculus. Dental calculus can be an alternative source of noninvasive, inexpensive, and specific dietary biomarkers.